2014
DOI: 10.1016/j.ejcdt.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma presenting as thoracic plasmacytoma – Two rare cases

Abstract: Multiple myeloma (MM) is a clonal proliferation of plasma cells with multiple osteolytic lesions. Multiple myeloma in the thorax is relatively uncommon. Hereby, we present 2 cases of multiple myeloma involving the thorax (1) in a 55 years old nonsmoker, female (2) and in a 45-years-old, smoker, male.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Similar to our case, a report by Saha et al reported cases of MM who presented with pneumonia-like respiratory symptoms associated with a mass lesion arising from the apex of the left lung. [6] In another report by Prasad et al, a case of MM with plasmacytoma of the lung had similar sign and symptom constellations except the lytic lesions were in the thoracic cage unlike our case, where the lytic lesions were evidenced in the skull. [7] The diagnosis of extramedullary thoracic plasmacytoma is particularly difficult when there is no thoracic vertebral or rib involvement.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Similar to our case, a report by Saha et al reported cases of MM who presented with pneumonia-like respiratory symptoms associated with a mass lesion arising from the apex of the left lung. [6] In another report by Prasad et al, a case of MM with plasmacytoma of the lung had similar sign and symptom constellations except the lytic lesions were in the thoracic cage unlike our case, where the lytic lesions were evidenced in the skull. [7] The diagnosis of extramedullary thoracic plasmacytoma is particularly difficult when there is no thoracic vertebral or rib involvement.…”
Section: Discussionsupporting
confidence: 72%
“…[5] Two cases of MM involving the thorax were reported from India. [6] The classic thoracic manifestations of MM are bony involvement of the thoracic cage. However, primary thoracic involvement by myeloma occurs in less than 1% of cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost 15%–30% of patients may develop extramedullary involvement during the course of MM. Although rare, thoracic involvement has been reported in patients with multiple myeloma in the form of a lung mass, diffuse reticulonodular infiltration, multiple pulmonary nodules, lymphadenopathy and mediastinal mass, tracheobronchial infiltration, and nodular pleural thickening with pleural effusion [ 6 ]. Pleural plasmacytomas are extremely rare and account for around 3–6% of extramedullary disease in MM patients [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A standard therapeutic guideline is not currently available and an individualized, multimodal approach using different strategies, such as advanced radiotherapy techniques, immunomodulatory agents (e.g., thalidomide, pomalidomide, and lenalidomide), and proteasome inhibitors (e.g., bortezomib, carfilzomib), is generally attempted. At the time of relapse, there is no clear rationale to prefer one drug class over another, and the therapeutic approach should take into account the previous lines of treatment as well as the duration of response in that patient [ 4 , 6 , 13 , 14 ]. The presence of extramedullary plasmacytomas in patients with multiple myeloma (MM) is associated with an adverse prognosis.…”
Section: Discussionmentioning
confidence: 99%